The effectiveness of consumption tax on the reduction of car pollution in China - Andres Arcila; Tao Chen; Xiaolan Lu (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2018)
Exposure to airborne pollution has substantial adverse health consequences (Cohen et al, 2004). Governments around the world have paid attention to this problem and started to take actions to mitigate it harmful effects. In this paper, we investigate how a change in the consumption tax structure affects car emissions by exploiting exogenous variation from a natural experiment that took place in China. Our results show that this tax policy, which doubled the imposition paid on cars with large engines, reduced the emissions of all the pollutants studied, with the most significant decrease of 11% noted in Particulate Matter and Carbon Monoxide.
Keywords: 330